PFAS contamination in soil and sediment: Contribution of sources and environmental impacts on soil biota - Ehsan, Mohammad Nazmul; Riza, Mumtahina; Pervez, Md Nahid; Li, Chi-Wang; Zorpas, Antonis A.; Naddeo, Vincenzo (Case studies in chemical and environmental engineering, 2024)
Per- and polyfluoroalkyl substances (PFAS) have been detected in soils worldwide, suggesting that soil serves as a substantial reservoir for these compounds. This paper provides a comprehensive overview of the origin of PFAS contamination in soil and sediment, as well as the environmental impacts associated with the distribution of PFAS in these mediums. In this review, we also discuss the effects of PFAS on soil microbes, plants, the terrestrial food web, sediment microbes, and benthic microorganisms. The highest concentration of PFAS was found in soils exposed to aqueous film-forming foam (AFFF), the PFAS manufacturing plants, and biosolids, compared to landfills, atmospheric deposition, and industrial discharge, which are the other three sources. Exposure to PFAS has demonstrated negative effects on the richness, diversity, and population structure of bacterial species. It has been observed to interfere with the regular functioning of soil microorganisms, microbes, and benthic organisms in sediment. Nevertheless, the current data is insufficient to grasp the complete spectrum of effects comprehensively. Moreover, the accumulation of PFAS in plants, vegetables, and earthworms is a cause for concern, as they can eventually enter the food chain through trophic transfer processes. Finally, we discuss the challenges and possible strategies that can be implemented to restrict the dispersion of PFAS in sediments and soil. [Display omitted]